'How Can Anyone Live Like That?' Exploring the Conscious and Unconscious Implications for Disabled People of any Change in Assisted Suicide Law. (17th April 2019) - Kane, Anne
Abstract : This paper explores the issue of assisted suicide in relation to disabled people from a psychosocial perspective. The implications, particularly the unconscious implications, for disabled people and for the psychosocial dynamics around disability if assisted suicide was made lawful in the UK are explored. Assisted suicide is the subject of persistent attempts at legal change and while not, in theory, specific to disabled people, the issue brings some of the psychosocial dynamics around impairment and disability into focus, illuminating the attitudes and emotions with which disabled people must try to live. Psychoanalytic ideas in relation to trauma, loss, mourning and containment are drawn upon with particular reference to the work of Freud, Klein, Bion and more contemporary thinkers such as Garland, Sinason and Rustin. The paper draws on three texts by disabled people in order to explore emotional responses to profound impairment. Attachment theory helps in considering varying narrative styles. Disability studies literature and legal, social and political contextual issues inform the psychosocial perspective applied in the paper.